Myelin Oligodendrocyte Glycoprotein (MOG) Antibody Positive Patients in a Multi-Ethnic Canadian Cohort - Cross, Helen; Sabiq, Farahna; Ackermans, Nathalie; Mattar, Andrew; Au, Shelly; Woodhall, Mark; Sun, Bo; Devonshire, Virginia; Carruthers, Robert; Sayao, Ana Luiza; Bhan, Virender; Schabas, Alice; et al. (Frontiers in Neurology, 2021)
Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease is a recently described central nervous system (CNS) inflammatory disorder with phenotypic overlap with Neuromyelitis Optica Spectrum Disorder (NMOSD). NMOSD seronegative patients, and those with limited forms of the disorder, become suspects for MOG antibody-associated disease. We describe a multi-ethnic population with MOG antibody seropositivity from the University of British Columbia MS/NMO clinic. AQP4-antibody seronegative patients presenting 2005 - 2016 with CNS inflammatory disease suspicious for NMOSD, and 20 MS controls, were retrospectively tested for MOG-IgG1 antibodies by live cell-based assay at Oxford Autoimmune Neurology Diagnostic Laboratory (UK) and by a commercial fixed cell-based assay at MitogenDx (Calgary, Canada). Additional MOG seropositive cases were identified through routine clinical interaction (2016-2018) using one of these laboratories. Clinical data was reviewed retrospectively. Retrospective testing identified 21 MOG seropositives (14 by live assay only, 3 by fixed assay only and 4 by both) representing 14% of the ‘NMOSD suspects’ cohort. One multiple sclerosis (MS) control serum was MOG seropositive. 20 additional MOG positive cases were identified prospectively. Of 42 patients (27 female), median disease onset age was 29 years (range 3-62; 9 pediatric cases), 20 (47%) were non-Caucasian and 3 (7%) had comorbid autoimmune disease. Most common onset phenotypes were optic neuritis (23, 55%; 8 bilateral) and myelitis (9, 21%; 6 longitudinally extensive) (Cortical encephalitis with seizures: 2). Moderate-severe onset in 64%, but 74% had good response to initial steroid therapy. Cumulative relapse probability for the MOG positive group at 1year was 0.428. Most had abnormal brain imaging, including cortical encephalitis and poorly demarcated subcortical and infratentorial lesions. Few “classic MS” lesions were seen. Optic nerve lesions (frequently bilateral) were long and predominantly anterior, but 5 extended to the chiasm. Spinal cord lesions were long and short, with involvement of multiple spinal regions simultaneously, including the conus medullaris. Our MOG seropositive patients display phenotypes similar to previous descriptions, including cortical lesions with seizures and conus medullaris involvement. Most patients relapsed, predominantly in a different CNS location from onset. Serologic data from two different cell-based antibody assays highlight the discrepancies between live and fixed testing for MOG antibodies.